Research on the comprehensive evaluation index system of social practice in Chinese universities based on the CIPP model - Yingping Nie; Qintong Lin; Wenlai Xia; Lihui Tu (PLoS ONE, 2026)
Social practice constitutes an essential aspect of talent development in higher education institutions, and the evaluation index system for social practice enables the quality of talent cultivation in these institutions to be determined. Grounded in the theoretical framework of the CIPP evaluation model, this study incorporates insights from 27 policy texts, core studies, and qualitative interview findings. It first identifies potential evaluation indicators for social practice, then gathers research samples via questionnaires and employs the Delphi method to assess the significance of these indicators. As a result, it establishes a social practice evaluation index system for higher education institutions, which includes four primary indicators, eleven secondary indicators, and thirty-seven tertiary indicators. Building upon this, the study utilizes the AHP to score the final evaluation index system and assign weights, thus completing the construction of the index system. The index system developed in this study not only concentrates on the process and scope of social practice activities, but also considers the internal and external factors that affect the implementation of social practice. Furthermore, it emphasizes the integration of formative and summative evaluations, offering valuable guidance for enhancing and improving social practice activities.